2017
DOI: 10.1007/s10661-017-5810-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the sustainability of solid waste management system—the case of Palestine

Abstract: Understanding the predictors of sustainability in solid waste management (SWM) systems can significantly contribute to eliminate many waste management problems. In this paper, the sustainability elements of SWM systems of interest are (1) attitudes toward separation at the source, (2) behaviour regarding reuse and/or recycling and (3) willingness to pay for an improved service of SWM. The predictors affecting these three elements were studied in two Palestinian cities: Ramallah and Jericho. The data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 31 publications
3
19
1
6
Order By: Relevance
“…In the study by Rodrigues et al, knowledge and waste management were correlated while no significant associations were denoted between knowledge and other statistical variables (18). Our findings also indicated a significant correlation between attitude and prior training on waste management, which corroborates with the results of Al-Khateeb et al (26), indicating the impact of this variable on students' attitudes toward waste recycling. According to the results of the present study, attitudes and other statistical variables represented no significant correlation.…”
Section: Analytical Sectionsupporting
confidence: 88%
“…In the study by Rodrigues et al, knowledge and waste management were correlated while no significant associations were denoted between knowledge and other statistical variables (18). Our findings also indicated a significant correlation between attitude and prior training on waste management, which corroborates with the results of Al-Khateeb et al (26), indicating the impact of this variable on students' attitudes toward waste recycling. According to the results of the present study, attitudes and other statistical variables represented no significant correlation.…”
Section: Analytical Sectionsupporting
confidence: 88%
“…However, other studies observed that knowledge and positive attitude alone did not support the proper recycling practice, while face-toface training leads to correct practice in solid waste recycling and source separation [114]. In a study on the residents of two Palestinian cities, it was observed that knowledge on waste management affects the willingness to pay for improved service of solid waste management, thus contributing to better waste management [115]. Therefore, organizations involved in municipal waste management are recommended to consider training programs to facilitate and clarify the process of home composting through brochures, video media, and cyberspace.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Booming economy, population growth, and consumption pattern change have greatly urged the production of domestic solid waste (DSW), especially in developing countries 1 3 . China has reported an 890% soaring of DSW from 1979 to 2018 4 and a continued growth rate of 8–10% per annum in the future 5 .…”
Section: Introductionmentioning
confidence: 99%